Pengaruh Kemampuan Individu Dan Komitmen Kerja Terhadap Kualitas Kerja Melalui Kepuasan Kerja Di Koperasi Jasa Bintang Karya Sejahtera Provinsi Sumatera Utara - Halawa, Sudiyarni; Bangun, Nirwana Br.; Razali, Muhammad (Journal of Innovative and Creativity, 2026)
This study aims to analyze the influence of individual ability and work commitment on work quality with job satisfaction as an intervening variable at Koperasi Jasa Bintang Karya Sejahtera in North Sumatra Province. The research focuses on: (1) the effect of work commitment on job satisfaction, (2) the effect of job satisfaction on work quality, (3) the effect of individual ability on work quality with job satisfaction as a mediating variable, (4) the direct effect of individual ability on work quality, (5) the direct effect of work commitment on work quality, (6) the effect of individual ability on job satisfaction, and (7) the effect of work commitment on work quality through job satisfaction. This study uses a quantitative approach with a survey method, utilizing questionnaires as the data collection instrument. The population consists of 316 employees, with a sample of 76 respondents selected using the Slovin formula. Data analysis techniques include multiple linear regression and mediation tests. The results indicate that both individual ability and work commitment have a positive and significant effect on job satisfaction and work quality. Moreover, job satisfaction is also proven to have a positive and significant impact on work quality. Job satisfaction is found to successfully mediate the effect of individual ability and work commitment on work quality. These findings highlight the importance of improving employee competencies and strengthening work commitment to enhance satisfaction and work quality effectively.